2008
DOI: 10.1002/gcc.20603
|View full text |Cite
|
Sign up to set email alerts
|

Allelic methylation bias of the RARB2 tumor suppressor gene promoter in cancer

Abstract: Retinoic acid receptor B2 (RARB2) is frequently inactivated in cancer. Methylation in the 5'-untranslated region and first exon is known to play a role; however, few studies have analyzed the detailed methylation pattern of the promoter region. We show that hypo- and hypermethylated alleles coexist in 5/11 cell lines in which RARB2 is inactivated. We present evidence supporting the mitotic transmission of these divergent methylation patterns and find a correlation between methylation divergence and heterozygos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…Aberrant hypermethylation of the RARbeta2 promoter has been principally reported in primary breast cancer and premalignant lesions [9,29]. In this study, we have shown that RARbeta2 promoter region undergoes hypermethylation in a 36.4% of primary breast tumors.…”
Section: Discussionmentioning
confidence: 73%
“…Aberrant hypermethylation of the RARbeta2 promoter has been principally reported in primary breast cancer and premalignant lesions [9,29]. In this study, we have shown that RARbeta2 promoter region undergoes hypermethylation in a 36.4% of primary breast tumors.…”
Section: Discussionmentioning
confidence: 73%
“…We tested this hypothesis using antisense oligodeoxynucleotides (ASO) to knockdown RARB2 mRNA levels in several RARB2-expressing tumor-derived cell lines, including A-549, NCI-H23, and NCI-H125. These cell lines were previously found to carry only unmethylated RARB2 alleles (Pappas et al, 2008). We found a correlation between the extent of knockdown and the inhibition of cell growth.…”
Section: Introductionmentioning
confidence: 63%
“…First, although large deletions of the chromosomal region 3p(14-23) carrying RARB2 (located at 3p21) have long been known to occur in lung cancer (WhangPeng et al, 1982;Naylor et al, 1987), intragenic mutations involving the remaining allele [the ''second-hit'' in Knudson's two-hit hypothesis (Knudson, 1971)] have not been reported [Houle, B., Pappas, J.J. and Bradley W.E.C., unpublished observations, and (Widschwendter et al, 2000)]. While RARB2 methylation has been reported by several groups including ours (Cote and Momparler, 1997;Cote et al, 1998;Bovenzi et al, 1999;Sirchia et al, 2000Sirchia et al, , 2002Virmani et al, 2000;Bovenzi and Momparler, 2001;Pappas et al, 2008) and may inactivate the remaining allele, the complete lack of mutations remains unusual as well as unexplained, unless RARB2 methylation occurs at a higher rate than is usual for ratelimiting mutations (Knudson, 2001). Second, although expression of classical tumor suppressor genes is very frequently inactivated in tumor cells, RARB2 remains expressed in about half of all lung, breast, and colon cancers.…”
Section: Introductionmentioning
confidence: 72%
“…However, few studies have analyzed the detailed methylation pattern of the promoter region [33,40-42,42], and to our knowledge, studies have not analyzed isolated alleles by sequencing only one subclone per bisulfite conversion reaction ( see Section 2.5.1). The vast majority of studies have used methylation-specific PCR, pooling potentially mixed populations of alleles together, as previously described in ref.…”
Section: Resultsmentioning
confidence: 99%